Mid-lumbar traumatic spondyloptosis without neurological deficit: A case report and literature review. Issue 12 (March 2020) - Xu, Feng; Tian, Zhisen; Fu, Changfeng; Yao, Liyu; Yan, Mengjie; Zou, Congcong; Liu, Yi; Wang, Yuanyi
Abstract: Introduction: Spondyloptosis is a form of vertebral dislocation and the most advanced form of spondylolisthesis. Traumatic spondyloptosis is usually caused by high-energy impact and results in unstable spine deformity and spinal canal deformation, which lead to severe spinal cord injury. Traumatic spondyloptosis is mostly reported in the lumbo-sacral junction, while it is rarely documented in mid-lumbar segments. To the best of the authors' knowledge, only 16 cases of mid-lumbar spondyloptosis have been described previously. Herein, we present a L3 to L4 spondyloptosis case that did not involve neurological deficit. Patient concerns: A 42-year-old man presented to the emergency department after an accident involving a fall. The patient developed severe back pain and spinal deformity, while his neurologic function remained intact. Radiological examinations indicated complete posterior vertebral dislocation at L3 to L4 and a fracture at the bilateral pelvic ischial tuberosity without major vessel injury or severe dura sac compression. Diagnoses: L3 to L4 complete vertebral dislocation, pelvic ischial tuberosity fracture. Interventions: For treatment, the patient underwent fracture reduction, L3 to L4 intervertebral fusion, and internal fixation 7 days post-injury. Outcomes: Postoperative digital radiography showed the correction of the spinal deformity. The patient was pain-free and fully rehabilitated 3 months after the surgery. At the 1-year follow-up, the patient was completely asymptomatic and had achieved normal alignment. Conclusions: We reported an L3 to L4 traumatic spondyloptosis case that involved intact neurology, which is the first-ever reported mid-lumbar spondyloptosis case that involved complete posterior column and neural sparing. For the treatment of traumatic spondyloptosis without neurological deficit, restoring stability and preventing secondary cord injury should be taken into consideration.